Gaya Bahasa Luqman dalam Mendidik Anak (Uslub Mustawa An-Nahwi) - Chotibul Umam; Muhammad Alghiffary (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2020)
This article aims to reveal Luqman's language style in educating his children. Language style is an alternative way of instilling knowledge in children. Oftentimes, the advice given by Stilistika is chosen as a tool because it can reveal Luqman's language style in educating children. Mustawa al-Ä«autÄ« is the focus of stylistic studies because it is a minimal domain in conveying messages perfectly. The Luqman story was chosen because it became an ideal education icon according to the Qur'an. Through the descriptive method, the results of the discussion are as follows: Declarative style contains three meanings, namely: meaning that indicates weakness and solitude, meaning makes something big look small, verbs continuous and future also be interpreted in the past. The interrogative style has two meanings, namely: showing warning and amazement. The style of presenting and ending contains two meanings, namely: tasywÄ«q and ifÄdatu al-ikhtiá¹£Äá¹£. Displacement style is communicated using three forms of displacement, namely: from á¸amir huwa to nahnu, from fi'il mudhari to fi`il madhi, and from the jumlah of ismiyyah to the jumlah of fi'liyyah.